La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Myriam Boucher + Followup - Boucher, Myriam (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)
The caesura in musical production caused by recent global lockdowns has made contemporary music’s crisis of societal relevancy more apparent than ever. Bringing together interviews with music curators, musicians, activist networks and institutional leaders, this book details existing practices and approaches, showing that change is possible but only if the recent wave of interest in curatorial practices, diversity and divestment from a white, European bourgeois aesthetic are taken seriously by the musical establishment. This expanded second edition of Taking the Temperature adds a new preface, five new interviews, as well as followups with previous interviewees. Radiating out from the Ultima Festival and Oslo, ..

Fracturing Patriarchal Objectivity through Electro-Pop: Purity Ring and the vicissitudes of sight - Watkinson, Philip (Performance Research, 2021)
This article examines the deviated modes of seeing in the work of Canadian electro-pop band Purity Ring. Bringing their recent music into conversation with the theory of Tim Ingold and Eugenie Brinkema, I suggest that Megan James and Corin Roddick perform seeing as a granular, augmented act that continually shapes the boundaries between our bodies and the world around us. Particular attention is paid to James and Roddick’s creative engagement with optical touch and the formal capability of music to engage affectively with the act of seeing.By integrating musical examples, Tallulah Fontaine’s artwork for the band and the poetry of Kiran Millwood Hargrave, this article offers an expanded reading experience that spans the textual, the aural and the visual. I argue that the political crux of Purity Ring’s performance of perception lies in them moving beyond a reactionary response to patriarchal objectivity and towards a creative refiguration of perception as a form of subjectivation. The eyes that Purity Ring instantiate do not passively observe the world; they change it, both consoled and engulfed by the vicissitudes of perception.